Bilateral Motor Responses to Transcranial Magnetic Stimulation in Preterm Children at 9 Years of Age - Valkama, A. Marita; Rytky, Seppo O.; Olsén, Päivi M. (Neuropediatrics, 2021)
Objective This study was aimed to evaluate motor tracts integrity in nondisabled preterm-born (PT) children at 9 years of age.Methods Overall, 18 PT and 13 term-born (T) children without motor disability were assessed by transcranial magnetic stimulation (TMS). Motor-evoked potentials (MEPs) were measured bilaterally from the abductor pollicis brevis (APB) and the tibialis anterior (TA) muscles. Muscle responses could be stimulated from all patients.Results Overall, 83.3 and 23.1% of PT and T children, respectively, had mild clumsiness (p = 0.001). One PT and three T children had immediate bilateral responses in the upper extremities. Seven PT children had delayed ipsilateral APB responses after left and ten after right TMS. Three controls had delayed ipsilateral responses. Ipsilateral lower extremity responses were seen in one PT after right and two PT children and one T child after left TMS. The results did not correlate to groups, genders, clumsiness, or handedness.Conclusion Children of PT and T may have bilateral motor responses after TMS at 9 years of age. Ipsilateral conduction emerges immediately or more often slightly delayed and more frequently in upper than in lower extremities.Significance Bilateral motor conduction reflects developmental and neurophysiological variability in children at 9 years of age. MEPs can be used as a measure of corticospinal tract integrity in PT children.
Keywords: clumsiness; motor-evoked potentials; preterm; transcranial magnetic stimulation